The maximum maximum of a martingale with given n marginals - Henry-Labordere, P; Obloj, J; Spoida, P; Touzi, N (2012)
We obtain bounds on the distribution of the maximum of a continuous martingale with fixed marginals at finitely many intermediate times. The bounds are sharp and attained by a solution to n-marginal Skorokhod embedding problem in Obloj and Spoida (2013). It follows that their embedding maximises the maximum among all other embeddings. Our motivating problem is superhedging lookback options under volatility uncertainty for an investor allowed to dynamically trade the underlying asset and statically trade European call options for all possible strikes and finitely-many maturities. We derive a pathwise inequality which induces the cheapest superhedging value, which extends the two-marginals pathwise inequality of Brown, Hobson and Rogers (1998). This inequality, proved by elementary arguments, is obtained by following the stochastic control approach of Galichon, Henry-Labordere and Touzi (2011).